Who Thinks, Feels. The Relationship Between Emotions, Politics and Populism - Donatella Bonansinga (Coordinamento SIBA, 2020)
There is a tendency both in academia and in popular understandings to posit emotions against rationality and to judge them as an expression of intellectual inferiority. This could not be more evident than in current accounts of populism, which often describe populist supporters as overtaken by passions rather than relying on rational deliberation. However these arguments hardly stand up to scientific scrutiny. As I will show by reviewing the state-of-the-art, advancements in disciplines such as political psychology have now provided systematic evidence of how, contrary to what is traditionally rooted in the public imaginary, emotions and cognition work in concert. If emotionality is an integral part of decision-making and is vital to any type of political engagement, the question we should rather ask is what is peculiar about the relationship between emotions and populism. In the second part of the article, I will explore how the emotional 'supply and demand' intersect in our contemporary societies, where capitalism, individualism and globalisation have created particular affective states that provide fertile ground for the populist appeal to resonate. By examining the emotions-populism relationship based on three broad dimensions - structural, subjective and communicative -, this article provides a multilevel analysis that unpacks the significance of emotions for the emergence, diffusion and success of populism.